2016
DOI: 10.17795/jjhr-37836
|View full text |Cite
|
Sign up to set email alerts
|

Alteration Effect of Exendin-4 on Oxidative Stress and Metabolic Disorders Induced by Bisphenol A in Adult Male Mice

Abstract: Background: Exendin-4 is a similar peptide to GLP-1 and can interfere with various receptors of GLP-1. Bisphenol A (BPA), as an endocrine disruptor chemical, is used in a wide range of plastic products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“… 44,45 Previous studies have shown a protective effect of PCA2 against oxidative stress, protecting against bisphenol A-induced apoptosis in islet cells and decreasing the MDA equivalents level in pancreas tissue. 46 Similarly, our data also revealed that PCA2 and its major metabolite HPPA protected against ox-LDL-induced oxidative stress. HPPA was less effective than PCA2 and only partly moderating the oxidative stress induced by ox-LDL, not being able to recover the cellular MDA equivalents level completely.…”
Section: Discussionsupporting
confidence: 73%
“… 44,45 Previous studies have shown a protective effect of PCA2 against oxidative stress, protecting against bisphenol A-induced apoptosis in islet cells and decreasing the MDA equivalents level in pancreas tissue. 46 Similarly, our data also revealed that PCA2 and its major metabolite HPPA protected against ox-LDL-induced oxidative stress. HPPA was less effective than PCA2 and only partly moderating the oxidative stress induced by ox-LDL, not being able to recover the cellular MDA equivalents level completely.…”
Section: Discussionsupporting
confidence: 73%
“…Anti-hyperglycemic effect of PCA2 combined with our observations at protein and mRNA level suggests that reduction in glucose level may be due to lowering of hepatic glucose production and/or stimulated insulin release followed by uptake by liver and muscle cells leading to decrease plasma glucose concentration. The ndings assume particular signicance as proanthocyanidin A type phenolics are reported to possess a broad spectrum of health benets, [18][19][20][21] foods containing proanthocyanidins reduce the risk of cardiovascular diseases, cancer, blood clotting, and protect against urinary tract infections. [22][23][24][25][26] For the rst time phyto-chemical investigations of the tender shoots of W. glabrata revealed active constituent PCA2 and support its use as traditional medicine for management of diabetes by the suggested lowering hepatic glucose production.…”
Section: Discussionmentioning
confidence: 99%
“…2) Procyanidin A2 (2), an oligomeric compound comprising catechin and epicatechin, also has a DDN scaffold and exhibits antioxidant, antibacterial and glucose homeostasis preventive activities. [3][4][5] Alzheimer's disease (AD) is one of the most common and devastating neurodegenerative diseases. The pathogenesis of AD is very complex.…”
Section: Introductionmentioning
confidence: 99%